Seasonal variations of bone metabolism and bone mineral density in collegiate alpine skiers - Sato, T.; Sakuraba, K.; Tsuchiya, Y.; Maruyama, S.; Ochi, E. (The Journal of Strength and Conditioning Research, 2018)
This study investigated the seasonal variations in bone metabolism, mineral density, and physical characteristics in collegiate alpine skiers. Twelve male subjects (20.6 ± 1.5 years) were evaluated for body composition, bone mineral density (BMD), serum levels of osteocalcin (OC), bone alkaline phosphatase (BAP), tartrate-resistant acid phosphatase 5b (TRACP-5b), parathormone, and 25-hydroxy vitamin D. We also measured the knee extensor and flexor strength, maximal power, and vertical jump. Measurements were conducted in the preseason period (T1), competitive period (T2), end-of-season period (T3), and resting period (T4). The percentage of body fat significantly increased from T1 to T2—T4 (p < 0.05), but lean body mass significantly decreased from T1 to T2—T4 (p < 0.05). Although BMD increased at T2 (0.9%) and T3 (0.8%), as compared with that at T1 (p < 0.05), BAP and OC decreased at T2 and T3, as compared with that at T1 (p < 0.05). Tartrate-resistant acid phosphatase 5b significantly increased from T1 to T2 (p < 0.05). We concluded that it is important to monitor bone metabolism markers and BMD of male alpine skiers throughout the season.